The Truth of the Deed of Granting Liability Rights to Lawyers That Isn't Genuine Positive Legal Perspective in Indonesia - Noor, Aslan; Kurnia, Agnes Adila; Dwika, Mohamad Bima; Fauzy, Farid Ahmad; Anugrah, M Reza (Faculty of Sharia and Islamic Law Institut Agama Islam Negeri Bone, 2023)
Mortgage Rights are security rights imposed on land rights, the granting of Mortgage Rights is always followed by a Deed of Granting Mortgage Rights (APHT), APHT regulates the terms and conditions regarding the granting of Mortgage Rights from debtors to creditors in connection with secured debts by Mortgage Rights. The Certificate of Enforcing Mortgage Rights (SKMHT) based on Article 15 paragraph (1) of the UUHT is one of the processes in granting Mortgage Rights made by Notaries and PPATs by following the applicable provisions by their positions. This research uses the juridical-normative method and descriptive-analytical research specifications. The results of the research on the validity of APHT based on the non-authentic SKMHT are that the Notary in making SKMHT must be based on the UUJN, while the PPAT in making SKMHT is based on PerKaban Number 8 of 2012. In practice, the Notary still makes SKMHT based on PerKaban Number 8 of 2012 and fills in the blank/format provided by the National Land Agency. so that the authenticity of the SKMHT made by the Notary disappears and the proof is less than perfect, if this happens, the SKMHT made by the Notary causes no legal consequences or null and void APHT which becomes an accessory agreement.